Corn fertilization with triple superphosphate in a Typic Hapludox soil under the residual effect of alternative phosphorus sources (Revista de Ciências Agroveterinárias, 2018)
In variable-charge soils, the use of alternative phosphorus sources may influence further soluble phosphate fertilization. This study aimed to evaluate phosphorus (P) availability for corn plants in response to triple superphosphate fertilization (TSP) in a Typic Hapludox (Oxisol) soil with residual P from alternative sources. The experiment was carried out in a greenhouse under a completely randomized design and 2x4x5 factorial scheme, with four replications. Treatments consisted of five TSP doses (0, 30, 60, 90, and 120 mg dm-3 P), and two sequential corn croppings with and without liming; the area was previously grown with Urochloa spp. and fertilized with precipitated phosphate-1 (PP1), precipitated phosphate-2 (PP2), natural reactive phosphate (NRP), and TSP at 120 mg dm-3. The P from TSP has its dynamics within the soil-plant system and fertilization efficiency in corn crops altered by the residual effect of P from alternative sources and by soil acidity correctives. The residual effects of PP2 and NRP, dry matter yield and P accumulation in corn were higher for TSP doses above 30 mg dm-3, being greater in the first cropping and in limed soils. Yet for PP2 and NRP residual effects, the highest soil availability of P was registered after the two sequential cropping in both acidity conditions, thus showing an enhanced residual effect.
Keywords: available phosphorus; phosphate residue; soil acidity